2016
DOI: 10.1186/s40064-016-3033-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of rectangular slit-inserted ultra-wideband tapered slot antenna

Abstract: In this paper, a tapered slot antenna capable of ultra-wideband communication was designed. In the proposed antenna, rectangular slits were inserted to enhance the bandwidth and reduce the area of the antenna. The rectangular slit-inserted tapered slot antenna operated at a bandwidth of 8.45 GHz, and the bandwidth improved upon the basic tapered slot antenna by 4.72 GHz. The radiation pattern of the antenna was suitable for location recognition in a certain direction owing to an appropriate 3 dB beam width. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…2) Inserted Slits: The use of inserted slits in tapered slot antennas was proposed by Kim and Choi [30] where it was shown that a significant increase in bandwidth was obtained with implemented slits of adequate size compared to the basic tapered slot antenna. A similar design was implemented on the Vivaldi antennas in order to obtain the required bandwidth while keeping a minimum antenna area.…”
Section: ) Printed Lens In Aperturementioning
confidence: 99%
“…2) Inserted Slits: The use of inserted slits in tapered slot antennas was proposed by Kim and Choi [30] where it was shown that a significant increase in bandwidth was obtained with implemented slits of adequate size compared to the basic tapered slot antenna. A similar design was implemented on the Vivaldi antennas in order to obtain the required bandwidth while keeping a minimum antenna area.…”
Section: ) Printed Lens In Aperturementioning
confidence: 99%
“…Communication Mode #2 is conducted by NB Antenna #2. In Mode #2, NB Antenna #2 is used to communicate in the mid-frequency band (5)(6)(7)(8). Figure 8 shows the S-parameter characteristics of NB Antenna #2.…”
Section: Communication Mode #2mentioning
confidence: 99%
“…Various UWB antennas [3][4][5][6][7][8] have been studied to obtain the wideband characteristic required for UWB communications. In [9,10], a reactive impedance surface (RIS) was used to broaden the impedance bandwidth, especially at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Optimized dimensions in (㎜) of proposed antenna dimensions of antenna [8] . The radiating patch is formed on the top side where as ground is on other side of substrate [14,15] .…”
Section: ⅱ Antenna Geometrymentioning
confidence: 99%